2018
DOI: 10.1080/1828051x.2018.1423581
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation of the environmental impact of cereal-based intensive beef finishing herds

Abstract: This study aimed to investigate the effect of beef category, feedstuffs self-sufficiency (SELF), crude protein (CPI) and phosphorus (PI) daily intake on the environmental impact of the beef fattening system typical of north-eastern Italy according to a partial Life Cycle Assessment. The reference unit was the batch (group of animals homogeneous for genotype, sex, fattening farm, finishing period). The study involved 245 batches (64 ± 34 heads) herded in 17 fattening farms. The system boundaries were set from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the present study the farms showing higher feed self-sufficiency levels showed lower GWP values. Positive correlations between the GWP and purchased concentrate consumption have been found in the present study, thereby highlighting the effect of purchased concentrates on the environmental impacts of beef production, as a result of LUC and transport-related emissions (Berton et al, 2018). The magnitude of the on-farm feed production emissions in the present study also appears to be closely linked to the amount of purchased feeds.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study the farms showing higher feed self-sufficiency levels showed lower GWP values. Positive correlations between the GWP and purchased concentrate consumption have been found in the present study, thereby highlighting the effect of purchased concentrates on the environmental impacts of beef production, as a result of LUC and transport-related emissions (Berton et al, 2018). The magnitude of the on-farm feed production emissions in the present study also appears to be closely linked to the amount of purchased feeds.…”
Section: Discussionsupporting
confidence: 74%
“…In this context, efficiency improvements for dairy farms, animal management and animal feeding are key aspects for the mitigation of the environmental impacts associated with dairy farming (de Boer et al 2011;Mostert et al 2018), other animal productions (Berton et al 2018;Vellinga et al 2011) and crops production for feed purposes (Tuomisto et al 2012;Zucali et al 2018). In a literature review by Baldini et al (2017), authors investigated recent studies on Life Cycle Assessment of milk production showing that there is still need of consistency in the assumptions and in the investigated inventory data in order to bring to comparability among studies.…”
Section: Introductionmentioning
confidence: 99%
“…The impact factors for the purchased feedstuffs were derived from Ecoinvent database (Ecoinvent Centre, 2015). The conversion of single compounds in the common unit of the impact category which they contribute was equal to that used in Berton et al (2018). The impact due the breeding period was derived from Pirlo et al (2016).…”
Section: Methodsmentioning
confidence: 99%